PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA (Studi pada Mata Pelajaran Bahasa Inggris Siswa Kelas VIII SMP Negeri 8 Pagar Alam) - Betty Helawati (UNIB Press, 2021)
The aims of this study to produce interactive multimedia learning to improve students’ outcome in English subject at VIII grade in SMP Number 8 Pagar Alam. This study uses a development design (Research and Development). The method used Borg and Gall design with 10 steps in research. The subjects of this study for limited scale test were students in class VIII.A and VIII.B of SMP Number 8 Pagar Alam with 16 students. And in wide scale test were students in class VIII.A and VIII.B of SMP Number 8 Pagar Alam with 32 students. The techniques of collecting the data uses the media assessment sheets and test for students’ outcome learning. Data analysis used mean score and t-test. The conclusions of this research were the development of an interactive multimedia learning could be used and effective to improve students’ learning outcomes in English subject. And the development of an interactive multimedia learning could improve students’ learning outcomes based on limited scale test and wide scale test at VIII grade of SMP Number 8 Pagar Alam in English subject